Enhanced production yields of rVSV-SARS-CoV-2 vaccine using Fibra-Cel® macrocarriers - Cohen, Noam; Simon, Irit; Hazan, Ophir; Tal, Arnon; Tzadok, Hanan; Levin, Lilach; Girshengorn, Meni; Mimran, Lilach Cherry; Natan, Niva; Baruhi, Tzadok; David, Alon Ben; Rosen, Osnat; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
The COVID-19 pandemic has led to high global demand for vaccines to safeguard public health. To that end, our institute has developed a recombinant viral vector vaccine utilizing a modified vesicular stomatitis virus (VSV) construct, wherein the G protein of VSV is replaced with the spike protein of SARS-CoV-2 (rVSV-ΔG-spike). Previous studies have demonstrated the production of a VSV-based vaccine in Vero cells adsorbed on Cytodex 1 microcarriers or in suspension. However, the titers were limited by both the carrier surface area and shear forces. Here, we describe the development of a bioprocess for rVSV-ΔG-spike production in serum-free Vero cells using porous Fibra-Cel® macrocarriers in fixed-bed BioBLU®320 5p bioreactors, leading to high-end titers. We identified core factors that significantly improved virus production, such as the kinetics of virus production, the use of macrospargers for oxygen supply, and medium replenishment. Implementing these parameters, among others, in a series of GMP production processes improved the titer yields by at least two orders of magnitude (2e9 PFU/mL) over previously reported values. The developed process was highly effective, repeatable, and robust, creating potent and genetically stable vaccine viruses and introducing new opportunities for application in other viral vaccine platforms.